Challenges of Migrating to Agile Methodologies. - Nerur, Sridhar; Mahapatra, Radhakanta; Mangalaraj, George (Communications of the ACM, 2005)
The article articulates the challenges that chief information officers and project managers must be cognizant of in their endeavors to embrace the agile philosophy of software development. It focuses on constantly changing software development methodologies owing to changing technologies and new demands from users. Several surveys demonstrate the growing popularity of agile methodologies in the field of software development. Past research shows that software development process changes represent complex organizational change phenomena and cannot be accomplished merely by replacing current tools and technologies with new ones. Uncertainties in the field of software development are further compounded by the diversity and unpredictability of people who engage in such tasks. A rationalized, engineering-based approach has dominated software development almost since its inception. Systems development in the traditional approach is guided by a life cycle model such as the waterfall model, the spiral model, or some variations of these.